Functional Band and Loop Space Maintainers in Children - V. Vinothini; A. Sanguida; A. Selvabalaji; G. S. Prathima; M. Kavitha (Hindawi Limited, 2019)
Premature loss of teeth in children leads to space loss and affects arch integrity. The band and loop space maintainer is used in majority of patients requiring single tooth space maintenance in both primary and mixed dentitions. It preserves the proximal dimensions, but it is nonfunctional. This paper describes a method to modify the conventional band and loop space maintainer into a functional one and reports its clinical application and follow-up in five children.